Gambaran Pengetahuan Remaja Putri tentang Genitalia Hygiene saat Menstruasi pada Siswi Kelas IX di SMP Negeri 3 Takalar Tahun 2025 - Yahya, Fajar Dhini; Nanda, Kiki Riskianti (JURNAL KESEHATAN DELIMA PELAMONIA, 2025)
Reproductive health in adolescents, particularly concerning genital hygiene during menstruation, is an essential aspect that is often overlooked. Lack of knowledge and awareness may lead adolescent girls to adopt improper hygiene practices, increasing the risk of reproductive tract infections. This study aimed to describe the knowledge of adolescent girls about genital hygiene during menstruation at SMP Negeri 3 Takalar. This was a descriptive quantitative study using a cross-sectional approach. The sample consisted of 42 ninth-grade female students selected through total sampling. Data were collected using a questionnaire and analyzed using univariate methods. The results showed that most respondents had moderate knowledge (57.1%), good knowledge (40.5%), and a small proportion had poor knowledge (2.4%). It can be concluded that the majority of adolescent girls at SMP Negeri 3 Takalar have a moderate level of knowledge regarding genital hygiene during menstruation, although continuous education is still needed to improve proper hygienic practices.